THE EFFECT OF GIVING BOILED KANDIS ACID WATER ON THE HEALING OF PERINEUM WOUNDS IN POST-POST MOTHERS - Izmi Fadilah Nasution; Hoirunnisa Tanjung; Litri Artiani Ginting; Sakinah Yusro Pohan; Mutia Sari Lubis; Tina Marito Harahap; Anni Mardiah Pohan (Journal of Maternity Care and Reproductive Health, 2026)
Perineal wounds are an area that is difficult to keep clean and dry, so it is important to care for perineal wounds to prevent infection, accelerate wound healing, and tissue repair. In addition, the problem of pain due to perineal stitches causes discomfort for postpartum mothers because it causes postpartum mothers to have difficulty defecating, urinating, and insomnia. Objective to determine the effect of giving kandis acid boiled water on perineal wound healing in postpartum mothers. The method: Quantitative research with a Quasi Experimental research method with the Only Posttest With Control Group Design approach with a sample of 20 postpartum mothers consisting of 10 people in the Treatment group and 10 people in the control group. The intervention treatment of giving Kandis Acid Boiled Water from the day of delivery until healing and observing the healing of perineal wounds of postpartum mothers both in the control group and the treatment group every day using the REEDA scale observation sheet. The results of the Normality test with the Shapiro-Wilk test were normally distributed, so Ho was rejected and Ha was accepted, namely the Effect of Giving Kandis Acid Boiled Water on Perineal Wound Healing. which means there is a significant difference between the duration of perineal wound healing with Kandis Acid Boiled Water and povidone iodine/betadine. There is an effect of giving Kandis acid boiled water on perineal wound healing in postpartum mothers. Suggestions for further researchers to be able to continue this research with different variables.